2012
DOI: 10.4161/cc.21281
|View full text |Cite
|
Sign up to set email alerts
|

Cistrome plasticity and mechanisms of cistrome reprogramming

Abstract: Mammalian genomes contain thousands of cis-regulatory elements for each transcription factor (TF), but TFs only occupy a relatively small subset referred to as cistrome. Recent studies demonstrate that a TF cistrome might differ among different organisms, tissue types and individuals. In a cell, a TF cistrome might differ among different physiological states, pathological stages and between physiological and pathological conditions. It is, therefore, remarkable how highly plastic these binding profiles are, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 131 publications
(210 reference statements)
1
11
0
Order By: Relevance
“…Extensive overlap with public ChIP-seq datasets confirmed that these sites are indeed composite enhancers, possibly evolved from extensive spread of transposable elements in mammals (21). Significantly, top factors comprise FOXA1 and AP2γ, known as "pioneer factors" for sex-steroid receptors (i.e., factors that open the chromatin allowing the landing of nuclear receptors on DNA) (29)(30)(31). We confirmed that silencing of these factors also reduces unliganded ERα occupancy.…”
Section: Significancesupporting
confidence: 56%
“…Extensive overlap with public ChIP-seq datasets confirmed that these sites are indeed composite enhancers, possibly evolved from extensive spread of transposable elements in mammals (21). Significantly, top factors comprise FOXA1 and AP2γ, known as "pioneer factors" for sex-steroid receptors (i.e., factors that open the chromatin allowing the landing of nuclear receptors on DNA) (29)(30)(31). We confirmed that silencing of these factors also reduces unliganded ERα occupancy.…”
Section: Significancesupporting
confidence: 56%
“…The LSD1 binding program has also been recently reported in mouse embryonic stem cells (mESCs) [54] , and although no particular connection between LSD1 and NRF1 was highlighted in this study, we analyzed the available data and observed that the NRF1 site is also significantly enriched between -150 bp and +50 bp relative to the TSS in these cells (p = 1e-42). In fact, the LSD1 binding map in human MCF7 and mouse ESCs differs at many sites (which is expected, especially at distal regions, since these two lines derive from different organisms and are completely different in many aspects [55] ), but they show remarkably similar binding profiles at many TSSs, including at those of classic NRF1 target promoters ( Figures S5D and S6 ). Taken together, our results show that the strong co-association of NRF1 motifs, NRF1 TF, and the LSD1 cofactor at −150/+50 bp regions can be observed in different cell lines and organisms, which supports a model in which cis-regulatory elements in these regions dictate strong and common cofactor signatures.…”
Section: Resultsmentioning
confidence: 89%
“…We speculate that presenilins may alter the binding of one or more of the transcription factors surrounding CREB sites, which in turn alters accessibility of CREB-regulatory elements specifically in these promoters. Examples supporting similar control of defining cistromes have been recently shown for other transcription factors (66).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, an intriguing possibility is that changes in the differentiation state caused by presenilin removal might be induced, at least in part, by presenilin-dependent changes in the CREB cistrome. Cistrome reprogramming events are emerging as important contributors to development and disease (66).…”
Section: Discussionmentioning
confidence: 99%